Application of Roadway Excavation and Supporting Technology in Coal Mining Engineering - Liu, Ruyuan (International Journal of Natural Resources and Environmental Studies, 2026)
With the increasing difficulty of coal mining and the rapid growth of science and technology, coal mining enterprises have higher requirements for roadway excavation and support technology. In practical applications, it is necessary to select the appropriate roadway driving and supporting technology to ensure the safety of underground production. Based on this, the factors and application characteristics of roadway driving and supporting technology in the process of coal mining are analyzed, and the practical application of roadway driving and supporting technology in coal mining engineering is also expounded.